Characteristics on Simple Sentences of Simple Present Tense Made by the Seventh Grade Students of SMPN 7 Samarinda - Yunita Sinaga (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2025)
This research was intended to know the characteristics of simple sentences of simple present tense made by the seventh grade students of SMP Negeri 7 Samarinda. This study used descriptive design. The population of the research was the seventh grade students of SMP Negeri 7 Samarinda with the total number of the population was 288 students, and the sample members taken was 58 students. The instrument of this study was a written test in the form of transformational sentences. The main tools to analyze the data were illustrations, facts, or features and statements. The research revealed the following findings: The characteristics of simple sentences in simple present tense made by the seventh grade students of SMP Negeri 7 Samarinda were: (a) omitting suffixes –s/es on main verbs for singular subject in affirmative forms, (b) mis forming the main verbs in present tense, (c) mis forming tense in simple present tense, (d) misusing auxiliary do/does in negative and interrogative form, (e) ) omitting auxiliary do/does in negative and interrogative forms and (f) misadding the auxiliary be and will.